Strong and ductile FeNiCoAl-based high-entropy alloys for cryogenic to elevated temperature multifunctional applications. (1st January 2023) - Zhang, Cheng; Yu, Qin; Tang, Yuanbo T.; Xu, Mingjie; Wang, Haoren; Zhu, Chaoyi; Ell, Jon; Zhao, Shiteng; MacDonald, Benjamin E.; Cao, Penghui; Schoenung, Julie M.; Vecchio, Kenneth S.; et al.
Abstract: The highly tunable properties of multi-principal element alloys, commonly known as high-entropy alloys (HEAs), provide a remarkable potential for the development of superior materials for critical structural applications that involve extreme conditions. However, the optimization of the properties of HEAs has been primarily limited to behavior at either low or high temperatures. Here, we report on a non-equiatomic, heterostructured, high-entropy alloy FeNiCoAlTaB which possesses remarkable combinations of mechanical properties across a wide range of temperatures from 77 K to 1073 K. The current metastable alloy presents good ductility and superior engineering tensile strengths of 2.2 GPa, 1.4 GPa, 800 MPa, and 500 MPa at 77 K, 298 K, 873 K, and 1073 K, respectively. This behavior is achieved by a synergic sequence of individual mechanisms that are activated at different temperatures. The alloy even displays pseudoelasticity at 77 K with an applied load up to 2 GPa. This work provides a methodology for tailoring structural heterogeneity and metastability in the design and fabrication of multifunctional HEAs that will outperform known metals and alloys over a wide range of temperatures. Graphical abstract: Image, graphical abstract